A nonparametric approach to portfolio shrinkage - Han, Chulwoo (Journal of Banking & Finance, 2020)
This paper develops a shrinkage model for portfolio choice. It places a layer on a conventional portfolio problem where the optimal portfolio is shrunk towards a reference portfolio. The model can accommodate a wide range of portfolio problems with various objectives and constraints, and its implementation is simple and straightforward. A data-driven method to determine the shrinkage level is offered. A comprehensive comparative study suggests the proposed model substantially enhances the performance of its underlying model and outperforms existing shrinkage models as well as the naïve strategy. The naïve strategy serves better as the reference portfolio than the current portfolio.